2021
DOI: 10.1002/cfp2.1131
|View full text |Cite
|
Sign up to set email alerts
|

A facet measure of money madness: A preliminary analyses of a new questionnaire

Abstract: This study reports on the development of a new, facet level questionnaire to measure "money madness" based on a well-established, four-factor model. It reviews the papers currently available to researchers on those with "money troubles" such as financial distress. In this study, 256 adult participants from diverse backgrounds, who were recruited online, completed a 52-item questionnaire designed to measure three facets of each of the four money factors: Security, Power, Love, and Freedom. They also completed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…There remains speculation as to why people become extreme, or compunctual spenders and savers, though there are a number of clinical speculations as to their origin and maintenance (Furnham & Horne, 2021). Equally, it is not clear how easy it is to change these beliefs or habits, though there are a number of books and programs dedicated to these issues (Ealy & Lesh, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There remains speculation as to why people become extreme, or compunctual spenders and savers, though there are a number of clinical speculations as to their origin and maintenance (Furnham & Horne, 2021). Equally, it is not clear how easy it is to change these beliefs or habits, though there are a number of books and programs dedicated to these issues (Ealy & Lesh, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…None, however, we believe have focused specifically on the spender–saver dimension, as most looked at personality correlates of associating money with different issues like love, freedom, security, and power. Based on the clinical literature we believe savers are more emotional stable, planful, and successful than spenders (Furnham & Grover, 2021; Furnham & Horne, 2021). Thus, we hypothesized that spenders would be more Neurotic ( H 1 ), Extraverted ( H 2 ), and less Conscientiousness ( H 3 ) than savers.…”
Section: Study 1: Bright-side Personalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps the most interesting results are those shown in Table 3 which examines the role of general money attitudes and the FDI. There are now a growing number of studies which have demonstrated that money beliefs are associated with a wide range of financial and nonfinancial behaviors (Furnham & Horne, 2021). There is a consistent theme in the results of these studies which is supported here: those who associated money with security, but not generosity/love, freedom, and power/status seem to be more stable, successful, and happy.…”
Section: Discussionmentioning
confidence: 99%